Realization of Labour in the Polish People’s Republic - Kamosiński, Sławomir (Studia Historiae Oeconomicae, 2012)
The article is an attempt to present the realization of labour in the Polish People’s Republic in the years 1945 – 1989. By realization of labour, I understand performance of work for the state employer. I contrasted the assumptions of work philosophy of the period with the real picture of performance of work in enterprises. I referred to organization of labour, technical culture of the staff, quality of labour, the remuneration system as an element of motivation to work efficiently, staff turnover and labour propaganda.